Pertanggungjawaban Pelaku Tindak Pidana Penggelapan Uang Angsuran Leasing (Studi Putusan Nomor 67/Pid.B/2021/Pn.Met) - Almaida Pubiana Mustika (Universitas Islam Balitar, Blitar, 2023)
The crime of embezzlement, which is regulated in Article 372 of the Criminal Code, is a criminal offense that spans various sectors and is committed by various groups of society. Both low and high levels of society have the potential to commit this crime. One of the important issues is how to deal with the responsibility of the perpetrators of embezzlement of leasing installments. This research using the normative legal research method analyzes Decision Number 67/Pid.B/2021/PN.Met and explored the basis for the judge's consideration in reaching a verdict in the case of embezzlement of leasing installment money. The results showed that in Decision Number 67/Pid.B/2021/PN.Met, the perpetrator of the crime of embezzlement of leasing installment money was proven guilty and violated Article 372 of the Criminal Code. As a result, the perpetrator was sentenced to imprisonment for 1 year and 7 months. The judge's reasoning in this decision involved several factors, including the evidence presented, witness testimony, the testimony of the defendant, the indictment and charges of the public prosecutor, as well as the elements contained in the prosecutor's charges. In addition, the judge's consideration also included aggravating and mitigating aspects of the defendant's actions. The decision provides guidance on how the various elements of evidence and testimony can form the basis of the judge's reasoning in deciding this type of case. In addition, this research underscores the importance of a comprehensive understanding of criminal law and applicable legal principles to ensure fairness in handling similar cases in the future.